RNA virome analysis of Haemaphysalis longicornis ticks collected in Hyogo, Japan - Aboshi, Alisa Rose; Matsumura, Ryo; Inumaru, Mizue; Sawabe, Kyoko; Watanabe, Mamoru; Sasaki, Toshinori; Kobayashi, Daisuke; Itoyama, Kyo; Isawa, Haruhiko (Japanese Journal of Infectious Diseases, 2025)
Tick-borne viruses are primarily transmitted to vertebrates by infected ticks during blood feeding and cause various diseases in humans and animals. Haemaphysalis longicornis is one of the main tick species responsible for human tick bites and is thought to be the primary vector of severe fever with thrombocytopenia syndrome, an important tick-borne viral disease in Japan. Although H. longicornis ticks pose a potential risk to humans in Japan, studies on tick-borne viral prevalence of this tick species in Japan are limited. In this study, we conducted RNA virome analysis of H. longicornis ticks collected in Toyooka City, Hyogo Prefecture, Japan. Two known viruses, Dabieshan tick virus and Hubei sobemo-like virus 15, and putative novel quaranjavirus-like sequences were detected. Additionally, assessments of endogenous viral elements (EVEs) related to the virus and virus-like sequences suggested putative novel quaranjavirus-like sequences existed in both RNA and DNA forms. However, we could not determine whether this quaranjavirus-like sequence was of viral origin and could not conclude whether the DNA forms of the quaranjavirus-like sequence existed as EVEs in ticks. This study provides new insights into the prevalence of tick-associated viruses in ixodid ticks and serves as a reference for future approaches to prevent tick-borne diseases.